Age‐related reproduction of female Mongolian racerunners (Eremias argus; Lacertidae): Evidence of reproductive senescence. Issue 5 (4th April 2019) - Ma, Li; Guo, Kun; Su, Shan; Lin, Long‐Hui; Xia, Yuan; Ji, Xiang
Abstract: The reproductive maturation hypothesis, the terminal investment hypothesis, and the senescence hypothesis are the most extensively evaluated hypotheses proposed to explain age‐related patterns of reproduction in iteroparous organisms. Here, we evaluated these hypotheses for the Mongolian racerunner ( Eremias argus ), a short‐lived lacertid lizard, by comparing reproductive traits between females that completed reproductive cycles under the same laboratory conditions in two consecutive years (2008 and 2009). Reproductive females gained linear size (snout‐vent length) not only as they got 1 year older but also during the breeding season. Larger females generally laid eggs earlier and invested more in reproduction than did smaller ones. Females switched from laying smaller eggs in the first clutch to larger eggs in the subsequent clutches but kept clutch size and postpartum body mass constant between successive clutches in a breeding season and between years. Females that laid more clutches or eggs in 2008 did not lay fewer clutches or eggs in 2009. Of the traits examined, only clutch frequency, annual fecundity, and annual reproductive output were susceptible to ageing. Specifically, the clutch frequency was reduced by 1.1 clutches, annual fecundity by 3.1 eggs and annual reproductive output by 1.0 g in 2009 compared with 2008. Our results suggest that the reproductive maturation hypothesis better explains patterns of reproduction in young or prime‐aged females of E. argus, whereas the senescence hypothesis better explains reproductive patterns in old females. The terminal investment hypothesis does not apply to any trait examined because no trait value was maximized in old females. Abstract : 1. We studied reproductive senescence in a lizard. 2. Clutch frequency, annual fecundity and annual reproductive output were susceptible to ageing. 3. The maturation hypothesis applies to young females, while the senescence hypothesis to old females. Abstract : Clutch frequency, annual fecundity, and annual reproductive output were susceptible to ageing. The reproductive maturation hypothesis better explains patterns of reproduction in young or prime‐aged females, whereas the senescence hypothesis better explains reproductive patterns in old females.